2011
DOI: 10.1021/bm200463e
|View full text |Cite
|
Sign up to set email alerts
|

Inducing β-Sheets Formation in Synthetic Spider Silk Fibers by Aqueous Post-Spin Stretching

Abstract: As a promising biomaterial with numerous potential applications, various types of synthetic spider silk fibers have been produced and studied in an effort to produce manmade fibers with mechanical and physical properties comparable to those of native spider silk. In this study, two recombinant proteins based on Nephila clavipes Major ampullate Spidroin 1 (MaSp1) consensus repeat sequence were expressed and spun into fibers. Mechanical test results showed that fiber spun from the higher molecular weight protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(104 citation statements)
references
References 59 publications
8
92
0
4
Order By: Relevance
“…22,23 Up to a limit of 50mm/s, XRD results show that the higher reeling speed also helps the orientation and formation of the silk network, while no influence on the secondary structure composition could be determined. [24][25][26] Premature invitro self-assembly poses one of the issues involved with the synthetic production of silk fibers.…”
Section: Figure1amentioning
confidence: 99%
“…22,23 Up to a limit of 50mm/s, XRD results show that the higher reeling speed also helps the orientation and formation of the silk network, while no influence on the secondary structure composition could be determined. [24][25][26] Premature invitro self-assembly poses one of the issues involved with the synthetic production of silk fibers.…”
Section: Figure1amentioning
confidence: 99%
“…In an attempt to promote favorable structural changes that have been shown to improve mechanical properties for other silks 9,12,43,[51][52][53] , post-spin stretching of AS W 3 fibers was carried out. Notably, organic solvent is typically employed in the post-spin stretching step because many silk-based AS fibers cannot withstand water penetration without being dissolved 9,11,12,15,42,44,45,59 .…”
Section: Post-spin Stretching Of As W 3 Fibersmentioning
confidence: 99%
“…Most studies characterizing post-spin stretching of silk-based fibers have reported carrying out this step manually with the use of forceps or tweezers 9,11,12,42 , with some reports of using controlled post-spin stretching apparatuses (e.g. 16,44 ).…”
Section: Post-spin Stretching Of As W 3 Fibersmentioning
confidence: 99%
See 2 more Smart Citations